Affordable, Social, and Substandard Housing and Mortality: The EPIPorto Cohort Study, 1999-2019 - Ribeiro, AI (2020)
Objectives. To examine the association between residence in different housing typologies and all-cause and cause-specific mortality, and to compare with the 25 × 25 risk factors defined by the World Health Organization. Methods. We used data from EPIPorto cohort (Porto, Portugal; n = 2485). We georeferenced and matched participants to a housing type—conventional, affordable, social, or substandard housing (locally called ilhas). We used Poisson regression models to estimate mortality rates and associations. Results. Age- and sex-adjusted mortality rates (per 100 000 person-years) were 713 (95% confidence interval [CI] = 584, 863) for individuals residing in conventional housing, and 1019 (95% CI = 637, 1551), 1200 (95% CI = 916, 1551), and 1239 (95% CI = 839, 1772) for individuals residing in affordable housing, social housing, and ilhas, respectively. After further adjustment, the associations between mortality and residence in social housing (rate ratio [RR] = 1.59; 95% CI = 1.22, 2.06) and in ilhas (RR = 1.64; 95% CI = 1.12, 2.33) remained. The association between disadvantaged housing and mortality was stronger than that observed for well-established risk factors such as hypertension, sedentariness, heavy drinking, manual occupation, or obesity. Conclusions. Disadvantaged housing is a major risk factor for mortality that should be accounted for by health policies and surveillance systems.